Analisis Tindak Tutur Direktif dalam Video Pembelajaran Sains di Sekitar Kita pada Kanal YouTube Pahamify - Malika Uswatun Hasanah; Rafanida Alyafatin; Amanda Ayu Ningrum; Astri Rivalianti; Himah Az Zahra; Asep Purwo Yudi Utomo; Arka Yanitama; Norma Eralita (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Pragmatics is a branch of linguistics that studies the intent of speech. The material of this research is directive speech acts. Directive speech act is one type of speech act used by speakers to tell others to do certain actions. This research analyzes the directive speech acts in the Science Around Us learning video on the Pahamify YouTube Channel. The approach used to examine this research is using theoretical and methodological approaches. The theoretical approach used is a pragmatic approach while the methodological approach used is a qualitative descriptive approach. This research method uses a pragmatic and descriptive qualitative approach. Data collection in this analysis is through listening and note-taking techniques, and using the derivative technique of simak bebas libat cakap. Then, the data analysis technique uses the commensurate technique. And using formal and informal data presentation techniques. The results show that there are various types of directive speech acts used by speakers, such as asking, commanding, ordering, inviting, asking, pleading, suggesting and forcing. The act of asking dominates, showing the speaker's effort to actively involve the audience. The findings indicate that directive speech acts play an important role in creating effective interaction in science learning through video media. This research contributes to a better understanding of more in-depth about language use in the context of online learning.